STUDY OF COPPER SULPHATE INDUCED MORTALITY TO FRESHWATER SNAIL, BELLAMYA BENGALENSIS (LAMARCK). - KAMBLE, N.A.; POTDAR, V.V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Induced toxicity of copper sulphate to freshwater snail Bellamya bengalensis showed mortality, which increased with increase in concentration and time of exposure to intoxicant. Experimental group of snails were intoxicated by using 1, 2, 3, 4 and 5 ppm concentrations of copper sulphate for 24, 48, 72 and 96 hrs of exposure. Mean LC50 value observed 0.36 ppm and Safe concentration was 0.056 ppm for snail Bellamya bengalensis.